On-site analysis of radioactive caesium in river water using portable gamma-ray survey meter - Satoshi Inose; Takayuki Mochimaru; Yuya Koike (Discover Applied Sciences)
Abstract Following the Fukushima Daiichi nuclear power plant accident, extensive research has been conducted on radioactive caesium isotopes (137Cs and 134Cs) by various groups. Using portable equipment, we conducted an on-site measurements of radioactive caesium, which significantly reduced the analysis time. In this study, the preparation of solid-phase extraction disk samples, effective count rate and detection efficiency calculation methods, and portable shielding for on-site radioactive caesium measurements using a portable gamma-ray survey meter (GSM) were investigated. The gamma-ray spectra of filter samples prepared according to the International Atomic Energy Agency standards and disk samples concentrated with radioactive caesium in soil leachate were measured using both the portable GSM and a high-purity germanium detector (HPGe). Yin's method was employed to calculate the radioactivity concentration of the disk samples using the portable GSM. The relative errors between the 137Cs activity concentration measured by the portable GSM and HPGe were kept within ± 5%. For the on-site radioactive caesium measurements, a self-designed shield was fabricated using a 3D printer and radiation shield materials to reduce the contribution of environmental radiation, such as cosmic and gamma-rays from radionuclides. On-site radioactive caesium analysis in river water was conducted using the portable GSM. An on-site analysis method for radioactive caesium in river water was investigated by combining the portable GSM with the solid-phase extraction disk concentration method. The proposed method enables straightforward quantitative analysis at environmental sites with a measurement time of over 1 h by utilizing an area compatible with the gamma-ray spectrum. Graphical abstract